In situ Ga-alloying in germanium nano-twists by the inhibition of fractal growth with fast Li+-mobility. Issue 70 (12th August 2019) - Yu, Zhaoliang; Yuan, Long; Wei, Yingjin; Li, Haibo; Meng, Xiangdong; Li, Yao; Endres, Frank
Abstract : The fractal growth-inhibited Ge0.90 Ga0.10 nano-twists exhibit higher Li + diffusion coefficient than the Ge fractal structures, promising for fast charging/discharging applications. Abstract : In this study, Ge0.90 Ga0.10 nano-twists were prepared by an in situ Ga-alloying method to inhibit the fractal growth of Ge. The mobility of Li + in the Ge0.90 Ga0.10 nano-twists was two orders higher than that in Ge. This advantage promotes fast charging of Li-ion batteries with the rate capability of 819 mA h g −1 at 16 A g −1 .